2014
DOI: 10.1016/j.scr.2013.10.005
|View full text |Cite
|
Sign up to set email alerts
|

JNK1 and 2 play a negative role in reprogramming to pluripotent stem cells by suppressing Klf4 activity

Abstract: Embryonic stem (ES) cells are pluripotent cells with the capacity for unlimited self-renewal or differentiation. Inhibition of MAPK pathways enhances mouse ES cell pluripotency characteristics. Compared to wildtype ES cells, jnk2(-/-) ES cells displayed a much higher growth rate. To determine whether JNKs are required for stem cell self-renewal or differentiation, we performed a phosphorylation kinase array assay to compare mouse ES cells under LIF+ or LIF- culture conditions. The data showed that activation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 45 publications
1
20
1
Order By: Relevance
“…In liver cancer, c-JUN forms a positive feedback loop with pluripotent genes to expedite cancer stemness [22]. However, the signaling network of c-Jun may be significantly different in MEFs [23]. Moreover, NuRD can interact with pluripotent genes and c-Jun in various ways [13, 2426], and thus depletion of MBD3 can influence the interaction between c-Jun and pluripotent genes.…”
Section: Discussionmentioning
confidence: 99%
“…In liver cancer, c-JUN forms a positive feedback loop with pluripotent genes to expedite cancer stemness [22]. However, the signaling network of c-Jun may be significantly different in MEFs [23]. Moreover, NuRD can interact with pluripotent genes and c-Jun in various ways [13, 2426], and thus depletion of MBD3 can influence the interaction between c-Jun and pluripotent genes.…”
Section: Discussionmentioning
confidence: 99%
“…It is to note that C-Jun amino-terminal kinase (JNK), which is another MAPK pathway enzyme, negatively regulates reprogramming [34]. Thus, we hypothesised that some growth factors present in the serum, such as fibroblast growth factors (FGF), could be barrier to enrichment of high-quality mouse iPS cells [35].…”
Section: Resultsmentioning
confidence: 99%
“…50 Recently it was shown that JNK1/2 signaling negatively regulates Klf4 activity. 51 JNK1/2 phosphorylates Klf4 and this inhibits Klf4 transcription and transactivation activity. Also pluripotency factors themselves are involved in the suppression of MAPK signaling.…”
Section: Discussionmentioning
confidence: 99%